Ecology of Karaulbazar Oil Processing Plant and Its Impact on the Environment - Mirzoyeva Istat Elmurodovna; Nematov Anvar Nusratovich (Genius Journals, 2022)
The following article deals with the details of the ecology of the Karaulbazar refinery and its impact on the environment.
Keywords: company; torch; Setalantepa; butane